Monte Carlo simulations of antiferromagnetic small particles - Vanessa S. Leite (Brazilian Journal of Physics, 2004)
We performed Monte Carlo simulations considering two different models for antiferromagnetic small particleswith Ising spins. The spins of the particle are disposed at the sites of the two dimensional arrays with coordinationnumbers z = 4 and z = 6, around a central spin. The core spins interact antiferromagnetically and thespins at the surface of the particle are disordered. In the first model, we consider an antiferromagnetic core surroundedby a disordered surface of the spin-glass type. In the second model, the core is still antiferromagnetic,but some bonds at the surface are broken. We determined the hysteresis curves, the zero-field-cooling (ZFC)and field-cooling (FC) curves. We have shown that the model with a disordered surface of the spin-glass typefits better the experimental measurements determined for the antiferromagnetic nanoparticles.